Numerical Investigation into Flutter and Flutter-Buffet Phenomena for a Swept Wing and a Curved Planform Wing - Mario Rosario Chiarelli; Salvatore Bonomo (International Journal of Aerospace Engineering)
The results of numerical studies carried out on high-aspect-ratio wings with different planforms are discussed: the transonic regime is analysed for a swept wing and a curved planform wing. The wings have similar aspect ratios and similar aerodynamic profiles. The analyses were carried out by CFD and FE techniques, and the reliability of the numerical aerodynamic results was proven by a sensitivity study. Analysing the performances of the two wings demonstrated that in transonic flight conditions, a noticeable drag reduction can be obtained by adopting a curved planform wing. In addition, for such a wing, the aeroelastic instability condition, consisting in a classical flutter, is postponed compared to a conventional swept wing, for which a flutter-buffet instability occurs. In a preliminary manner, the study shows that, for a curved planform wing, the high speed buffet is not an issue and at the same time notable fuel saving can be achieved.